Expression and function of the chemokine receptor CCR7 in thyroid carcinomas. - Sancho, M; Vieira, J; Casalou, C; Mesquita, M; Pereira, T; Cavaco, B; Dias, S; Leite, V (2006)
The chemokine receptor CCR7 plays a critical role in lymphocyte and dendritic cell trafficking into and within lymph nodes, the preferential metastatic site for papillary (PTC) and medullary (MTC) thyroid carcinomas. In order to determine a possible role for CCR7 in mediating the metastatic behaviour of thyroid carcinomas, we analysed its expression in normal and tumoral thyroid tissues of different histotypes and studied the in vitro effects of its activation by the CCR7 ligand, CCL21. Using real-time quantitative-PCR, we observed that CCR7 expression was higher in PTCs and MTCs than in follicular and poorly differentiated thyroid carcinomas. CCR7 expression was ninefold higher in classic compared with follicular variants of PTCs, and its expression in MTCs was significantly correlated with lymph node metastases. Immunohistochemical staining for CCR7 showed protein expression in neoplastic thyroid cells, with higher intensity in PTCs, MTCs and their lymph node metastases (LNMs). We further showed that CCL21 stimulation of a CCR7-expressing thyroid tumour cell line (TPC-1) promotes cell proliferation and migration, and the chemotactic effect of CCL21 in these cells involves actin polymerization, increased beta1-integrin expression and increased matrix metalloproteinase secretion. Taken together, our results demonstrate that CCR7 activation on thyroid carcinoma cells by CCL21 - a chemokine abundantly expressed in lymph nodes - favours tissue invasion and cell proliferation, and therefore may promote thyroid carcinoma growth and LNM.